Mandibular movements and bite force in Alzheimer's disease before and after new denture insertion - Campos, C. H.; Ribeiro, G. R.; Stella, F. [UNESP]; Rodrigues Garcia, R. C.M. (Wiley, 2017)
Chewing impairment has been observed in elders with Alzheimer's disease (AD); however, it is unknown whether oral rehabilitation can improve their masticatory function. This study evaluated the influence of new removable prostheses on chewing function of patients with AD. Participants using removable dentures were divided into two groups: patients with mild AD (77·2 ± 5·8 years, n = 16) and controls (76·0 ± 4·4, n = 16). All participants received general dental treatment and new total and/or partial removable prostheses. After 2 months of adaptation to the new dentures, chewing was evaluated by the following parameters: masticatory cycle time (CT), cycle velocity (CV), and opening (OA) and closing mandibular angles (CA), registered by a kinesiographic device. Maximum bite force (MBF) was assessed using a strain sensor. Evaluations were performed at baseline and after insertion of the new prostheses. A mixed model (α = 5%) was used for within- and between-subject analyses. After insertion of new prostheses, CT was reduced, and CV and MBF were increased in both groups (P < 0·05). There were no changes in OA or CA (P > 0·05). Compared to controls, elders with AD showed higher CT and reduced MBF and CV both at baseline and after insertion of new prostheses (P < 0·05). However, OA and CA did not differ between groups (P > 0·05). Insertion of new removable prostheses improved masticatory function in elders with and without AD, but patients with mild AD still had reduced chewing parameters compared to controls.
Keywords: Alzheimer's disease; applied kinesiology; bite force; chewing function; cognitive impairment; mastication